2011
DOI: 10.1257/aer.101.3.442
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Regulation and Labor Reallocation: Evidence from the Clean Air Act

Abstract: This paper uses newly available data on plant level regulatory status linked to the Census Longitudinal Business Database to measure the impact of changes in county level environmental regulations on plant and sector employment levels. Estimates from a variety of specifications suggest a strong connection between changes in environmental regulatory stringency and both employment growth and levels in the affected sectors. The preferred estimates suggest that changes in county level regulatory status due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(117 citation statements)
references
References 6 publications
2
115
0
Order By: Relevance
“…A related literature examines the employment effects of environmental regulation/protection where some studies find job losses (Henderson 1996, Khan 1997and Greenstone 2002, others find virtually no employment effects (Berman and Bui 2001, Morgenstern et al 2002and Cole and Elliott 2007 while Bezdek et al (2008) look at six states in the US and find a large positive jobs effects of environmental protection. More recently, Gray et al (2013) examine whether EPA regulations affect labor demand in the pulp and paper industry whilst Walker (2012) …”
Section: Literature Reviewmentioning
confidence: 99%
“…A related literature examines the employment effects of environmental regulation/protection where some studies find job losses (Henderson 1996, Khan 1997and Greenstone 2002, others find virtually no employment effects (Berman and Bui 2001, Morgenstern et al 2002and Cole and Elliott 2007 while Bezdek et al (2008) look at six states in the US and find a large positive jobs effects of environmental protection. More recently, Gray et al (2013) examine whether EPA regulations affect labor demand in the pulp and paper industry whilst Walker (2012) …”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, prior work has shown that while nonattainment designation reduces ambient concentrations of particulates, it does so at the cost of some economic competitiveness (Greenstone, 2002;Greenstone, List, and Syverson, 2012;Walker, 2011Walker, , 2012. Therefore, nonattainment may also contribute to declining economic conditions which may impact longrun earnings capacity of children born into those counties.…”
Section: Econometric Specificationmentioning
confidence: 99%
“…For example, nonattainment designation influences production decisions of firms (Greenstone, 2002;Walker, 2011), and these may have consequences for the broader economic community (Walker, 2012). This being said, the estimates from Walker (2011Walker ( , 2012 suggest that the effect of nonattainment designation on the overall labor market to be small. Additionally, a regression of contemporaneous county level per capita income on CAAA enactment, as presented in Table 6, failed to detect an effect, which also suggests at most a minor effect on the economy.…”
mentioning
confidence: 99%
“…There is evidence that environmental regulation also affects employment growth in regulated industries in the US [12]. Moreover, the costs of sectoral reallocation borne by individual workers may emerge not only in unemployment, but also in earnings losses after job changes [13].…”
Section: Competing Interestsmentioning
confidence: 99%